TREATMENT OF PYOMETRA IN FEMALE DOGS USING PROSTAGLANDIN F2α ± ANTIPROGESTIN (MIFEPRISTONE) - SHAH, M A; PANDE, N; SHAH, I A; AGRAWAL, R; SHARMA, U; GHUMAN, S P S (The Indian Journal of Animal Reproduction, 2016)
The female dogs confirmed for pyometra by history, clinical examination, ultrasonography and blood sampling were subjected to prostaglandin F2α (PGF2α) therapy with or without mifepristone, an antiprogestin (n=6 in each group). Following treatment, 11 out of 12 animals were successfully treated and recurrence till next estrous cycle was observed only in one case. The clinical signs uterine diameter and hemato-biochemical parameters were normalized by day 14 post onset of treatment in both the groups (p<0.05). By day 7, plasma progesterone decreased (p<0.05) in group receiving PGF2α alone, but increased in group receiving antiprogestin plus PGF2α. Briefly, mifepristone appears to be a safe and promising option for opening the cervical canal in closed pyometra cases of dogs and if used in combination with PGF2α, a success rate of upto 100% for the treatment of either type of pyometra can be expected in the absence of ovarian cysts.